Fifth Year Pre-service Science Teachersû Struggles with and Learning About Teaching Science Through a-Year-Long Field Experience - Faikhamta, Chatree (Kasetsart Journal of Social Sciences, 2011)
Field experiences are components of any teacher education program in which pre-service teachers learn how to teach in real situations. This study sought an understanding of 33 fifth year pre-service science teachers’ struggles with and learning about teaching science during their one-year field experience. This qualitative study based on an interpretative paradigm was drew upon written reflections, focus group interviews and observations of seminar sessions. Data analysis was inductive involving categorical aggregation, followed by a search for data correspondence and patterns to bring it to conclusion. Problematic issues for most of pre-service science teachers were unclear learning outcomes in lesson plans, rarely probing students’ prior knowledge, classroom management, and misconception in science concepts. Despite the struggles they experienced, pre-service science teachers had learned and broaden their pedagogical content knowledge. The recognitions of patterns of pre-service science teachers’ struggles and learning could be seen to be a basis for reflecting on and rethinking about the components of science teacher preparation program.